(untitled) (Journal of Parents and Teachers, 2025)
If there is one thing that is present in human life and history, albeit in different ways for each individual, both in terms of their own experiences and their way of conceiving it, it is love, almost always associated with happiness. But what happens when there is an “addiction” to love, a dependence on the loved one? This is when jealousy arises, those feelings that stem from our thoughts and, ultimately, from our idea of love. This article proposes some of the beliefs or fears that underlie this idea, some examples that allow us to identify these feelings, and some activities to deal with this experience, as well as suggestions for a more psychologically healthy experience of love.